2006
DOI: 10.1111/j.1366-9516.2006.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the native provenance of invasive fireweed (Senecio madagascariensis Poir.) in the Hawaiian Islands as inferred from phylogenetic analysis

Abstract: Accurate identification of weedy species is critical to the success of biological control programs seeking host-specific control agents. Phylogenetic relationships based on internal transcribed spacer region (ITS1, ITS2) DNA sequence data were used to elucidate the most likely origin and taxonomic placement of Senecio madagascariensis Poir. (fireweed; Asteraceae) in the Hawaiian archipelago. Putative S. madagascariensis populations from Madagascar, South Africa, Swaziland, and Hawaii were included in the analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…Fireweed has variable growth habits and leaf shapes dependant on the type of soil and habitat, (Le Roux et al 2006). Genetic analyses of fireweed in Australia showed a close match with the S. madagascariensis complex from South Africa and a slight difference from S. madagascariensis from Madagascar (Scott et al 1998).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Fireweed has variable growth habits and leaf shapes dependant on the type of soil and habitat, (Le Roux et al 2006). Genetic analyses of fireweed in Australia showed a close match with the S. madagascariensis complex from South Africa and a slight difference from S. madagascariensis from Madagascar (Scott et al 1998).…”
Section: Introductionmentioning
confidence: 95%
“…Genetic analyses of fireweed in Australia showed a close match with the S. madagascariensis complex from South Africa and a slight difference from S. madagascariensis from Madagascar (Scott et al 1998). Molecular analysis of Hawaiian fireweed populations showed that they also match populations from South Africa more closely than populations from Madagascar and Swaziland (Le Roux et al 2006). Hawaiian populations are thought to have arrived in carpet grass seed shipments from Australia (Motooka et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Studies that compare genetic structures of invasive populations and populations in the native range can help pinpoint the area of origin as well as elucidating patterns of colonisation and pathways of spread (Le Roux et al 2006). Do invaders come from areas with similar climatic characteristics?…”
Section: Introductionmentioning
confidence: 99%
“…The dominant invader was S. madagascariensis, which represented 14.7% 6 1.4% fractional cover across all plots in managed MSDF after ungulate exclusion (k ¼ 1.89 6 0.34 yr À1 , 95% CI ¼ 1.55-2.81 yr À1 , n ¼ 6). This species is native to southern Africa and Madagascar (Le Roux et al 2006). It is a prolific seed producer and capable of rapid population growth (Sindel and Michael 1988).…”
Section: Discussionmentioning
confidence: 99%